(untitled) - Sharpe, Pamela J. (Thành phố Hồ Chí Minh, 2006)
This is a valuable study guide for students preparing for the English as aoreign language test. This shorter version of Barron's full-size "TOEFL iBTest Prep Manual" has also been thoroughly revised and updated to preparetudents for the new internet-based test. It presents three model TOEFL iBTs,ll with explanations or example answers. The author also provides anverview of the new test format and extensive test-taking advice. The audioDs present audio prompts for the Listening, Speaking, and Writing sectionsn the book's practice tests.
Keywords: English language,Test of English as a foreign language,English language; Textbooks for foreign speakers,Study guides,Examinations,Study guides